Bone Diseases: Current Approach and Future Perspectives in Drug Delivery Systems for Bone Targeted Therapeutics - Chindamo, Giulia (2020)
Bone diseases include a wide group of skeletal-related disorders that cause mobility limitations and mortality. In some cases, e.g., in osteosarcoma (OS) and metastatic bone cancer, current treatments are not fully effective, mainly due to low patient compliance and to adverse side effects. To overcome these drawbacks, nanotechnology is currently under study as a potential strategy allowing specific drug release kinetics and enhancing bone regeneration. Polymers, ceramics, semiconductors, metals, and self-assembled molecular complexes are some of the most used nanoscale materials, although in most cases their surface properties need to be tuned by chemical or physical reactions. Among all, scaffolds, nanoparticles (NPs), cements, and hydrogels exhibit more advantages than drawbacks when compared to other nanosystems and are therefore the object of several studies. The aim of this review is to provide information about the current therapies of different bone diseases focusing the attention on new discoveries in the field of targeted delivery systems. The authors hope that this paper could help to pursue further directions about bone targeted nanosystems and their application for bone diseases and bone regeneration.